1983
DOI: 10.1007/bf00433266
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of bone and skin during recovery after cyclophosphamide administration

Abstract: The effects of cyclophosphamide were studied 2, 5 and 9 days after terminating a two-week every-second-day intraperitoneal medication in young, male rats. The cytostatic effect was assessed by counting white blood cells (WBC) in arterial blood. WBC counts were reduced by 72% of control values at 2 days and regained normal values at 9 days after an overshooting leucocytosis at 5 days. Compared to control animals, the treated rats had significantly reduced body weights, metaphyseal bending strength and longitudi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 8 publications
3
10
0
Order By: Relevance
“…Earlier investigations have shown that high intraperitoneal doses of cyclophosphamide causes significantly reduced synthesis and solubility of collagen in bones and in skin wounds of rats (Wie & Beck 1980). These findings were confirmed by the present observations as far as collagen solubility of implant connective tissue and collagen formation in bone and implants are concerned.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Earlier investigations have shown that high intraperitoneal doses of cyclophosphamide causes significantly reduced synthesis and solubility of collagen in bones and in skin wounds of rats (Wie & Beck 1980). These findings were confirmed by the present observations as far as collagen solubility of implant connective tissue and collagen formation in bone and implants are concerned.…”
Section: Discussionsupporting
confidence: 92%
“…Fourty-eight male, outbred Wistar/Af/Han/Mol SPF rats aged 27 days, with a median initial weight of 72 (71-75) g were used. This is the same material as that used in a previous paper dealing with the mechanical properties of bone and skin during recovery after cyclophosphamide treatment (Wie et al 1980).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations